2003
DOI: 10.1099/ijs.0.02303-0
|View full text |Cite
|
Sign up to set email alerts
|

Detection and characterization of Pasteuria 16S rRNA gene sequences from nematodes and soils

Abstract: Various bacterial species in the genus Pasteuria have great potential as biocontrol agents against plant-parasitic nematodes, although study of this important genus is hampered by the current inability to cultivate Pasteuria species outside their host. To aid in the study of this genus, an extensive 16S rRNA gene sequence phylogeny was constructed and this information was used to develop cultivation-independent methods for detection of Pasteuria in soils and nematodes. Thirty new clones of Pasteuria 16S rRNA g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 9 publications
1
16
0
1
Order By: Relevance
“…A similar analysis applied to P. penetrans (Atibalentja et al 2000) proved, predictably, its relatedness to the cladoceran parasite, and also their positioning within the genus Bacillus. Using a number of different isolates of Pasteuria spp., Duan et al (2003) confirmed the positioning within the low G+C Gram-positive genera and, in particular, with the family "Alicyclobacillaceae". Fortunately, the differences in host range and morphometrics that had resulted in the designation of two other presumptive species, P. thornei and P. nishizawae were borne out in this analysis by genetic differences large enough to be significant.…”
Section: Taxonomy and Phylogenysupporting
confidence: 73%
See 1 more Smart Citation
“…A similar analysis applied to P. penetrans (Atibalentja et al 2000) proved, predictably, its relatedness to the cladoceran parasite, and also their positioning within the genus Bacillus. Using a number of different isolates of Pasteuria spp., Duan et al (2003) confirmed the positioning within the low G+C Gram-positive genera and, in particular, with the family "Alicyclobacillaceae". Fortunately, the differences in host range and morphometrics that had resulted in the designation of two other presumptive species, P. thornei and P. nishizawae were borne out in this analysis by genetic differences large enough to be significant.…”
Section: Taxonomy and Phylogenysupporting
confidence: 73%
“…from infected nematodes and the soil by Duan et al (2003) allowed the design of Pasteuria-specific PCR primers. The resulting amplification fragments shared highly conserved restriction enzyme sites not found in any of the non-Pasteuria sequences that were interrogated in silico.…”
Section: S Rrna Gene Fragmentsmentioning
confidence: 99%
“…from around the globe, but there is very little understanding of the genetic variation between and within populations. Previous studies have focused on the position of P. penetrans in the bacterial kingdom (9,31,34) and the use of consensus 16S rRNA gene sequences (6,7,18) to differentiate between species and populations of Pasteuria (5,16,33). However, this information has not been extensively supported with sequence data from protein-encoding genes, which potentially provide an additional source of discrimination, with the exception of one study examining partial coding sequences of some genes in P. ramosa populations (32), as well as a recent study of genes encoding collagen-like proteins in this species (22a).…”
mentioning
confidence: 99%
“…The Pasteuria sp. was identified as P. penetrans based on the 16S ribosomal profile (Duan et al, 2003;Waterman et al, 2006). It was logical to expect nematode suppression in this 10-yrmonoculture field, but the nematodes were present at damaging levels making the field unproductive.…”
mentioning
confidence: 99%